Prospek dan Tantangan Indonesia dalam Menghadapi Liberalisasi Jasa Kepariwisataan - Adhiningasih Prabhawati (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2017)
Abstract The challenges and constraints faced by tourism in Indonesia such as issues related to infrastructure, human resources and environmental protection need to be overcome and handled appropriately and properly. More importantly, in today’s trade liberalization era, Indonesia must also have prepared itself to deal with it, especially liberalization of trade in tourism services, both at global and regional tingkat. Therefore, it is imperative that the Government of Indonesia make every possible attempt and devise good strategies to enhance the competitiveness of the tourism sector. The cooperation related to tourism are also very necessary between stakeholders from relevant agencies, those in the tourism business and the community living around the tourist areas. Not least the importance of cooperation between Indonesia with ASEAN countries and international organizations concerned with tourismhave to be done in order to create a positive impact on sustainable tourism in Indonesia. Keywords: tourism, liberalizations,strategies, the competitiveness